Using Conceptual Models of Teaching to Incorporate a Dog into a Self-Contained Classroom for Students with Severe Emotional or Behavioral Disorders: A Research-Based Intervention - Anderson, Katherine L.; Olson, Myrna R. (Journal of the American Academy of Special Education Professionals, 2006)
Described in this article is an empirical study that examined the effects of a dog in a self-contained classroom for students with severe emotional or behavioral disorders. The authors illustrate how the design of the study was based upon the integration of three conceptual models (ecological systems approach, social-cognitive approach, and cognitive-behavioral approach) and indicate that these approaches contributed to the positive results achieved. Across an eight-week period of time, observational and interview data revealed that the dog’s placement in the classroom improved students’ attitudes toward school, contributed to their emotional stability and ability to manage their own behaviors, and facilitated students’ learning of lessons in responsibility, respect, and empathy that enhanced their interactions with adults and peers.